2017
DOI: 10.1136/jim-2017-000457
|View full text |Cite
|
Sign up to set email alerts
|

Two Microrna Signatures for Malignancy and Immune Infiltration Predict Overall Survival in Advanced Epithelial Ovarian Cancer

Abstract: MicroRNAs have been established as key regulators of tumor gene expression and as prime biomarker candidates for clinical phenotypes in epithelial ovarian cancer (EOC). We analyzed the coexpression and regulatory structure of microRNAs and their co-localized gene targets in primary tumor tissue of 20 patients with advanced EOC in order to construct a regulatory signature for clinical prognosis. We performed an integrative analysis to identify two prognostic microRNA/mRNA coexpression modules, each enriched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Given the oncogenic function of miR-328 in ovarian cancer, we sought to determine whether there is a relationship between the level of miR-328 expression and the prognosis in human patients with ovarian cancer. Korsunsky and colleagues have profiled miRNA expression in 19 EOC and 13 benign ovarian masses using TaqMan OpenArray (34). We reanalyzed these data (GSE81873) and found that the miR-328 level is higher in EOC than benign tissues (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the oncogenic function of miR-328 in ovarian cancer, we sought to determine whether there is a relationship between the level of miR-328 expression and the prognosis in human patients with ovarian cancer. Korsunsky and colleagues have profiled miRNA expression in 19 EOC and 13 benign ovarian masses using TaqMan OpenArray (34). We reanalyzed these data (GSE81873) and found that the miR-328 level is higher in EOC than benign tissues (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the traditional immunohistochemistry immunoscoring approach remains suboptimal because of lacking a consistent standard and limited number of biomarkers assessed simultaneously. 34 Recently, molecular profiling-based approaches and signatures have been used to infer immune infiltration, such as mRNAs, 31 microRNA 35 and DNA methylation. 36 lncRNA, a recently identified key players of genome regulatory network, has also been found to play critical roles in the development and activation of immune cells, and may, therefore, serve as a specific molecular marker for tumor-infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of infiltrating cells may influence the tumour cells' HLA expression, as we previously described [40]. In a study involving epithelial ovarian cancer (another immune-privileged organ), miR-22 was similarly associated with the presence of an intra-tumoural immune infiltrate [54].…”
Section: Discussionmentioning
confidence: 77%